Lebarkan Sayap Penjualan Melalui Marketplace - Fahsa Urfaini Aghniya; Adeh Ratna Komala (Journal of Economics, Management, Business and Accounting (JEMBA), 2022)
The development of increasingly advanced technology requires business actors to keep up with existing changes. The use of the internet in Indonesia is widely used for the economic field, namely, helping business actors to market their products, provide product information to consumers, and make sales and purchases online. This development affects the growth of the marketplace in Indonesia, consumers are more attracted by the marketplace because it is more practical, can be done anywhere and modern. This research method, using descriptive method. Descriptive research is research conducted to determine the value of independent variables, either one or more (independent) variables without making comparisons, or connecting with other variables. In this study, there were 200 MSME business actors who gave their assessments of the e-commerce marketplace. The results obtained from this research are that the marketplace can provide facilities so that MSME business actors can market their products more broadly globally, can increase sales and facilitate buying and selling transactions to consumers. This study aims to introduce micro, small and medium business actors to several available marketplaces and utilize these marketplaces to expand market access.